1990
DOI: 10.1002/cne.902940106
|View full text |Cite
|
Sign up to set email alerts
|

Cluster organization and response characteristics of the giant fiber pathway of the blowfly Calliphora erythrocephala

Abstract: Intersegmental descending neurons (DNs) link the insect brain to the thoracic ganglia. Iontophoresis of cobalt or fluorescent dyes reveals DNs as uniquely identifiable elements, the dendrites of which are situated within a characteristic region of the lateral deutocerebrum. Here we demonstrate that DNs occur as discrete groups of elements termed DN clusters (DNCs). A DNC is a characteristic combination of neurons that arises from a multiglomerular complex in which the main components of each glomerulus are a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
5

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 48 publications
2
50
1
5
Order By: Relevance
“…4 H). It has been suggested that this type of escape behavior can be induced in white-eyed mutants only Bacon and Strausfeld, 1986;Milde and Strausfeld, 1990;Fayyazuddin et al, 2006). In contrast, our experiments with transgenic animals expressing CaMKII in GFS or in cholinergic neurons show that it is not the eye color (red in our case), but probably the genetic background (w 1118 ) that is the decisive factor in eliciting this escape behavior.…”
Section: Expression Of Camkii-t287d In Gf Neurons Disrupts Lightinduccontrasting
confidence: 68%
“…4 H). It has been suggested that this type of escape behavior can be induced in white-eyed mutants only Bacon and Strausfeld, 1986;Milde and Strausfeld, 1990;Fayyazuddin et al, 2006). In contrast, our experiments with transgenic animals expressing CaMKII in GFS or in cholinergic neurons show that it is not the eye color (red in our case), but probably the genetic background (w 1118 ) that is the decisive factor in eliciting this escape behavior.…”
Section: Expression Of Camkii-t287d In Gf Neurons Disrupts Lightinduccontrasting
confidence: 68%
“…In contrast to locusts (for review, see Rowell 1988), however, not much is known about their physiology in flies, despite an extensive anatomical description (e.g. Strausfeld 1989;Milde and Strausfeld 1990;Strausfeld and Gronenberg 1990;Gronenberg and Strausfeld 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, not all of them showed obvious responses to visual stimuli, including both light-off and dark-field expansion. A study of the blowfly Calliphora erythrocephala found that the GDN would spike when simultaneously given a mechanical stimulus to the antenna and a light-off stimulus to the eye (Milde and Strausfeld, 1990). Fig.…”
Section: Response Of the Gdn To Multimodal (Simultaneous Visual And Mmentioning
confidence: 99%
“…Descending neurons (DNs) mediating this alternative escape pathway have not yet been identified. Possible candidates are other members of the GDN cluster that comprise a system of at least eight parallel channels, which with the GDN likely share at least the same lobula-derived inputs (Strausfeld and Bacon, 1983;Milde and Strausfeld, 1990). More recent studies on the Drosophila GDN have shown that looming visual stimuli elicit subthreshold responses (Mu et al, 2012a), as do acoustic stimuli detected by the antenna's Johnston's organ (Tootoonian et al, 2012) or direct mechanical stimulation of the antenna (Lehnert et al, 2013).…”
Section: Introductionmentioning
confidence: 99%